Uji Efektivitas Nutrisi Ab Mix dan Jenis Media Tanam terhadap Produksi Hasil Setek Batang Tanaman Mint (Mentha spicata L.) pada Sistem Wick Hidroponik - Fatulillah, Puan; Syah, Bastaman; Laksono, Rommy Andhika (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 7 No 1 (2022)DO - 10.24843/JITPA.2022.v07.i01.p03, 2022)
Mentha spicata L. or commonly known as spearmint is an herbaceous plant that has many benefits in this pandemic period, but land limitations that become a production problem can be overcome with the use of hydroponics wick system. This study aims to get the best combination treatment of AB Mix nutrients and planting media to the production of mint plant stems (Mentha spicata L.) in hydroponic wick systems. The research was conducted at the screen house of SMKN Pertanian Karawang, East Karawang Subdistrict, Karawang Regency in June to July 2021. The research method used is an experimental method with a randomized design group (RAK) of single factors consisting of 12 treatments with 3 repeats. The data is analyzed with a variety analysis and if the 5% F test shows a real different result, then continued with the DMRT (Duncan Multiple Range Test) test at the level of 5%. Paramater observed included plant height (cm), number of leaves (strands), wet weight of plants (grams), and plant growth rate (cm/week). The results showed that there was a noticeable influence on the observation parameters of plant height aged 2, 3, 4, 5, and 6 MST, the number of leaves aged 5 and 6 MST, wet weight of plants, wet weight of plants without roots and plant growth rate.